2022
DOI: 10.3389/fpsyg.2022.836865
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lexicality, Frequency, and Markedness on Mandarin Tonal Categorization

Abstract: While the Ganong lexicality effect has been observed for phonemic and tonal categorization, the effects of frequency and markedness are less clear, especially in terms of tonal categorization. In this study, we use Mandarin Chinese to investigate the effects of lexicality, tone frequency and markedness. We examined Mandarin speakers’ tonal categorization of tokens on all possible tonal continua with one end being a word and the other being a tonotactic gap (i.e., an unattested syllable-tone combination). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…An ambiguous sound midway between a /t/ and /d/ was more likely to be identified as /t/ in a context like "?ask", and /d/ in a context like "?ash", because "task" is a real word (while *"dask" is not), and "dash" is a real word (while *"tash" is not). Similar Ganong-type lexical bias effects have been observed with different phoneme pairs (Connine, Titone, Deelman, & Blasko, 1997;Pitt, 1995), in different word positions (Pitt & Samuel, 1993, 1995, with words of varying lengths (Pitt & Samuel, 2006), and in tones (Fox & Unkefer, 1985; T. H. Yang, Jin, & Lu, 2019). Likewise, in phoneme restoration studies, for example, listeners report hearing a word as intact despite the presence of noise obscuring particular sounds in the word (Warren, 1970).…”
Section: Lexical Influence In Phonetic Encodingsupporting
confidence: 53%
See 4 more Smart Citations
“…An ambiguous sound midway between a /t/ and /d/ was more likely to be identified as /t/ in a context like "?ask", and /d/ in a context like "?ash", because "task" is a real word (while *"dask" is not), and "dash" is a real word (while *"tash" is not). Similar Ganong-type lexical bias effects have been observed with different phoneme pairs (Connine, Titone, Deelman, & Blasko, 1997;Pitt, 1995), in different word positions (Pitt & Samuel, 1993, 1995, with words of varying lengths (Pitt & Samuel, 2006), and in tones (Fox & Unkefer, 1985; T. H. Yang, Jin, & Lu, 2019). Likewise, in phoneme restoration studies, for example, listeners report hearing a word as intact despite the presence of noise obscuring particular sounds in the word (Warren, 1970).…”
Section: Lexical Influence In Phonetic Encodingsupporting
confidence: 53%
“…This suggests that, at least outside of a sentential context and syntactic, semantic, and pragmatic clues, listeners do not have particularly robust categorical responses at the end points. While direct comparison across our two experiments is not possible because of the lack of a shared dependent variable, the results are reminiscent of T. H. Yang et al (2019) and Fox and Unkefer (1985), both of which observed more categorical perception of (non-merging)…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations